POPULATION STRUCTURE Nerita lineata (GASTROPODS) IN MANGROVE FOREST OF SUNGAI CINGAM VILLAGE OF RUPAT SUB DISTRICT OF BENGKALIS REGENCY - Nabilah Jauharah; Syafruddin Nasution; Efriyeldi Efriyeldi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbstractNerita lineata is one type of mollusc from the family Neritidae which has economic value. This research was conducted in Maret 2018 located at the mangrove forest of Sungai Cingam Village, Rupat Sub District, Bengkalis Regency. This research was aimed to determine the population structure N. lineata which cover density, distribution patterns and size distribution. This research used survey method and sampling location determined by purposive sampling. Measurement of water quality was done by in situ and ex situ which consist of physics and chemical parameters. Condition of N. lineata habitat was muddy sand, sandy mud and sandy. Sediment organic matter was medium and very high 2.97-30.58 %. The water quality parameters are still support for the life of the gastropods. The average density was 3.45 ind/m2. The highest density was in station II and the lowest in station I. The distribution pattern was grouping. The size of the gastropods found has a length 10-26 mm.Keyword: Population Structure, Density, Distribution Patterns, Nerita lineata.